2006
DOI: 10.1111/j.1365-3083.2006.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Role of Chloroquine and Pyrimethamine in Plasmodium yoelii 17XL Infected Mice

Abstract: Chloroquine (CLQ) and Pyrimethamine (PYR) are used for the treatment of malaria and some autoimmune diseases; although their mechanism of action is only partially understood, their therapeutic effectiveness in the second case has been attributed to their ability to increase apoptosis of T lymphocytes. In view of the potential for immunomodulation during malaria chemotherapy, we investigated the effects of CLQ and PYR treatment on lymphocyte apoptosis and cytokine expression during infection with blood‐stage Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Artemisinins also have the ability to induce immunosuppression by inhibiting delayed-type hypersensitivity, lymphocyte proliferation, and a rise in antibody level (51). Immune deviation caused by chloroquine and other antimalarial drugs has been reported (52,53). We found that the plasma levels of the proinflammatory cytokines TNF and IFN-␥ increased in P. berghei ANKA-infected mice ( Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Artemisinins also have the ability to induce immunosuppression by inhibiting delayed-type hypersensitivity, lymphocyte proliferation, and a rise in antibody level (51). Immune deviation caused by chloroquine and other antimalarial drugs has been reported (52,53). We found that the plasma levels of the proinflammatory cytokines TNF and IFN-␥ increased in P. berghei ANKA-infected mice ( Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The obtained strain, having 80 % viability, was centrifuged at 1,500 rpm for 5 min, as previously reported (Ramos-Avila et al 2007; Spencer-Valero et al 1998; Lewis-Hughes and Howell 1984; Mons et al 1983); the pellet containing about 1 × 10 7 infected red blood cells (iRBCs) was suspended in 1 mL RPMI and immediately used for intraperitoneally inoculating five BALB/c mice, each administered with an average of 2 × 10 6 iRBCs. Parasitemia in all infected animals was monitored by Wright staining of blood smear, showing that mice became parasitized by the second to sixth day after infection, and that parasitemia levels increased slowly until animals died 10–12 days after having been infected (Ramaiya et al 1987; Smalley and Butcher 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Externalisation of phosphatidylserine was detected by annexin-V-FLUOS (Roche Diagnostics, Basel, Switzerland), as described previously 24. Briefly, 1 x 10 6 spleen cells were suspended in 200 µL reaction buffer (10 mM HEPES/NaOH, pH 7.4; 140 mM NaCl and 5 mM CaCl 2 ) and 2 µL of annexin-V-FLUOS.…”
Section: Methodsmentioning
confidence: 99%